الفروق اللغوية بين الكلمات المترادفة في المعجم العربي بين يديك من كلمة " سَوءَة" إلى كلمة "شُغْل" وكيفية الاستفادة منها في تعليم اللغة العربية للناطقين بغيرها - SOBIRIN; ABDURRAHIM (Rayah Al-Islam, 2016)
Language is a pattern or symbols which are tools of knowledge, and language is also the most important means for mutual understanding and tolerance between community members in all places or aspects of life. Language is a communication tool for sharing ideas, feelings, and sensitivities to achieve certain goals between two or more people, and Arabic is the most spoken language in semitic language groups, and this language is one of the most used languages ​​in world. Arabic is a universal language, and is an indication of its universality, the existence of tandems or synonyms in Arabic. The purpose of this study is to reveal the linguistic differences between the synonym words contained in Al-Mu'jam Al-'Arobi Baina Yadaiik from the word "سَوءَة" to the word "شُغل" - as a sample- and know the right strategy or way to its application in the teaching of Arabic for non-Arabs. This study method uses an analytical descriptive approach based on analysis of reality, and relies on the scientific method to obtain data, information and facts needed in analyzing linguistic differences between synonyms in the Baina Yadaik Arabic dictionary using research tools, namely content analysis. This study has a number of results, the most important of which is the existence of phenomena of synonyms and language differences in the Baina Yadaik Arabic language dictionary, and that each word has a meaning that is possibly consistent and may not, and the most appropriate strategy for teaching this stage is At -Ta'lim Al-Mubasyir and At-Ta'alum At-Ta'awunii.